2017
DOI: 10.1186/s13195-017-0309-z
|View full text |Cite
|
Sign up to set email alerts
|

N-truncated Aβ4–x peptides in sporadic Alzheimer’s disease cases and transgenic Alzheimer mouse models

Abstract: BackgroundThe deposition of neurotoxic amyloid-β (Aβ) peptides in plaques in the brain parenchyma and in cerebral blood vessels is considered to be a key event in Alzheimer’s disease (AD) pathogenesis. Although the presence and impact of full-length Aβ peptides such as Aβ1–40 and Aβ1–42 have been analyzed extensively, the deposition of N-terminally truncated Aβ peptide species has received much less attention, largely because of the lack of specific antibodies.MethodsThis paper describes the generation and cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
44
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 39 publications
4
44
1
Order By: Relevance
“…3b, d). As demonstrated in our previous study [79], the levels of the N-truncated Aβ4-40 peptides were low compared to full-length Aβ peptides in 5xFAD mice. In the SDS-soluble brain fractions of 12-month-old animals, Aβ4-40 levels were approximately 70-fold and 1500-fold lower than Aβ1-40 and Aβ1-42 levels (Fig.…”
Section: Genetic Deletion Of Adamts4 Lowers Aβ4-x and Increases Apps supporting
confidence: 73%
See 4 more Smart Citations
“…3b, d). As demonstrated in our previous study [79], the levels of the N-truncated Aβ4-40 peptides were low compared to full-length Aβ peptides in 5xFAD mice. In the SDS-soluble brain fractions of 12-month-old animals, Aβ4-40 levels were approximately 70-fold and 1500-fold lower than Aβ1-40 and Aβ1-42 levels (Fig.…”
Section: Genetic Deletion Of Adamts4 Lowers Aβ4-x and Increases Apps supporting
confidence: 73%
“…While Aβ peptides truncated at various N-terminal residues have been detected in brain tissue and cerebrospinal fluid samples of AD patients [6,40], subsequent studies have largely confirmed that Aβ4-42 and peptides with a pyroglutamate modification at position 3 (AβpE3-42) are particularly abundant [45,50,51,58,59,68]. Recently, two studies reported novel Aβ4-x-specific antibodies and the consistent finding that in the brains of AD patients and mouse models Aβ4-x peptides were largely confined to amyloid plaque cores, which are composed of the most insoluble, fibrillar Aβ peptides in β-sheet conformation [11,79]. In accordance, biophysical studies have demonstrated that Aβ4-x peptides rapidly assembled into soluble oligomers and fibrillar, high-molecular-weight aggregates [7,11,56].…”
Section: Introductionmentioning
confidence: 91%
See 3 more Smart Citations